2017
DOI: 10.1186/s12886-017-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic dacryocystorhinostomy with an otologic T-type ventilation tube in repeated revision cases

Abstract: BackgroundTo compare the frequency of appearance of complications, anatomical success and functional success after conventional endoscopic dacryocystorhinostomies (EN-DCRs) or EN-DCR with otologic T-Type ventilation tube combined with silicone tube intubation in repeated revision cases.MethodsTwenty-two patients who had epiphora and recurrent dacryocystitis after at least a previous failed revision DCR as well as 22 patients receiving conventional EN-DCR only were enrolled in the study between January 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…All our modified revised or primary modified Ex-DCR cases had both anterior and posterior sacco-mucosal flaps that may have contributed to the high success rates. Although some alternative approaches have been suggested for the treatment of failed cases, such as nasolacrimal recanalization (84.4%) [ 14 ], traditional approaches regarding the success rates of rDCRs revealed that rEE-DCR with silicone tube intubation has been reported to have a success rate of about 82.0% [ 15 ]. In the present Ex-DCR revision, none of the cases, except for 6 patients with atrophic sacs, required stent implantation, and the success rate was higher with the aid of sufficient bony opening in a proper location and anterior sacco-mucosal suspension.…”
Section: Discussionmentioning
confidence: 99%
“…All our modified revised or primary modified Ex-DCR cases had both anterior and posterior sacco-mucosal flaps that may have contributed to the high success rates. Although some alternative approaches have been suggested for the treatment of failed cases, such as nasolacrimal recanalization (84.4%) [ 14 ], traditional approaches regarding the success rates of rDCRs revealed that rEE-DCR with silicone tube intubation has been reported to have a success rate of about 82.0% [ 15 ]. In the present Ex-DCR revision, none of the cases, except for 6 patients with atrophic sacs, required stent implantation, and the success rate was higher with the aid of sufficient bony opening in a proper location and anterior sacco-mucosal suspension.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Demarco et al [33], concluded that revision endoscopic DCR after failed external surgery is a safe technique of low morbidity, permitting effective resolution of the lacrimal obstructions. As the revision endoscopic DCR has a high rate of failure, the usage of a T-type ventilation tube can significantly improve the success rate of surgery [34].…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время многие авторы применяют для профилактики рецидива после операции биканаликулярную интубацию дакриостомы [24][25][26].…”
Section: применение лакримальных имплантатовunclassified